Healthcare providers' perceptions and experiences of kangaroo mother care for preterm infants in four neonatal intensive care units in China: a qualitative descriptive study - Qian Cai; Qian Cai; Yunxian Zhou; Mengxia Hong; Danqi Chen; Danqi Chen; Xinfen Xu (Frontiers Media S.A., 2024)
BackgroundKangaroo mother care (KMC) is an evidence-based intervention that can effectively reduce morbidity and mortality in preterm infants, but it has yet to be widely implemented in health systems in China. Most qualitative studies on KMC for preterm infants focused on the experiences and influencing factors from the perspective of preterm infant parents, while neglecting the perspective of healthcare providers, who played a critical role in guiding KMC practice. Therefore, this study aimed to explore the perceptions and experiences of healthcare providers regarding their involvement in KMC implementation for preterm infants to promote the contextualized implementation of KMC.MethodsA descriptive qualitative approach was adopted. A purposive sampling was used to select healthcare providers involved in KMC implementation in the neonatal intensive care units (NICUs) as participants from four tertiary hospitals across four cities in Zhejiang Province, China. Face-to-face semi-structured interviews were conducted to collect information. Thematic analysis was employed to analyze the data.ResultsSeventeen healthcare professionals were recruited, including thirteen nurses and four doctors in the NICUs. Four themes and twelve subthemes emerged: different cognitions based on different perspectives (acknowledged effects and benefits, not profitable economically), ambivalent emotions regarding KMC implementation (gaining understanding, gratitude and trust from parents, not used to working under parental presence, and concerning nursing safety issues), barriers to KMC implementation (lack of unified norms and standards, lack of systematic training and communication platform, insufficient human resources, and inadequate parental compliance) and suggestions for KMC implementation (improving equipment and environment, strengthening collaboration between nurses and doctors, and support from hospital managers).ConclusionsDespite acknowledging the clinical benefits of KMC, the lack of economic incentives, concerns about potential risks, and various barriers hindered healthcare providers' intrinsic motivation to implement KMC in NICUs in China. To facilitate the effective implementation of KMC, hospital managers should provide bonuses and training programs for healthcare providers, while giving them recognition and encouragement to enhance their motivation to implement KMC.